New disciplines for domestic support - Glauber, Joseph W.; Laborde Debucquet, David; Piñeiro, Valeria (Instituto Interamericano de Cooperación para la Agricultura, 2021)
One of the hallmark accomplishments of the Uruguay Round Agreement on Agriculture (AoA) was the inclusion of agriculture in a system of multilateral rules and disciplines, including disciplines governing domestic support. Under those provisions, domestic support was capped based on support levels in a historical base period and then reduced over the implementation period of the agreement32. The AoA also encouraged Members to reform agricultural support towards minimally production- and trade-distorting support by exempting those measures from reduction commitments according to criteria laid out in Annex 2 of the AoA (the Green Box).